Pengendalian Kualitas dengan Metode Statistical Quality Control untuk Mengurangi Jumlah Produk Rusak pada Mustofa Bakery di Sukoharjo - Julia Alfi Puan Ariani; Sunarso Sunarso (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Mustofa Bakery is one of the businesses in Sukoharjo that operates in the food sector. The purpose of this study is to analyze product quality control using the Statistical Quality Control (SQC) method to reduce the number of damaged products and analyze the factors that cause product damage at Mustofa Bakery. The type of data used in this study is quantitative data. The data source used in this study is secondary data. Data collection methods by interview and observation. The data analysis technique used in this study uses the Statistical Quality Control (SQC) method. Based on the results of the research that has been done, it can be concluded that in March, April, and October it still exceeds the standard limit of production damage that has been set by Mustofa Bakery in Sukoharjo by 2%. The application of quality control with SQC can reduce the number of damaged products at Mustofa Bakery in Sukoharjo, proven to be true. The results of the Pareto Diagram of the types of damage that often occur are damage due to burning, 1,719 breads or 35.25%, damage due to inappropriate shape, namely 1,607 breads or 32.96%, and damage due to inappropriate texture as much as 1,550 breads or 31.79%. The results of the cause-and-effect diagram (fishbone) of the factors of product damage that occurred at Mustofa Bakery in Sukoharjo occurred due to machines, humans, methods, and raw materials.